p‐Orbital Ferromagnetism Arising from Unconventional O− Ionic State in a New Semiconductor Sr2AlO4 with Insufficiently Bonded Oxygen - Xu‐Guang Zheng; Chao‐Nan Xu; Tomoki Uchiyama; Ichihiro Yamauchi; Tomasz Galica; Eiji Nishibori; Ying Chen (Advanced Science)
Abstract Oxygen in solids usually exists in an O2− ionic state. As a result, it loses its magnetic nature of a single atom, wherein two unpaired electrons exist in its outer 2p orbitals. Here, it is shown that an unconventional stable ionic state of O− is realized in a new semiconductor material Sr2AlO4, leading to an intrinsic p‐orbital ferromagnetism stable until ≈900 K. Experimental and theoretical investigations have clarified that one‐fourth of the oxygen atoms in Sr2AlO4 are insufficiently bonded in the crystal structure, resulting in a unique O−‐state and p‐orbital ferromagnetism. To date, the O− state is reported to exist only in non‐equilibrium conditions, and p‐orbital magnetism is only suggested in impurity bands with small ferromagnetic moments. The present work provides a new route for creating ferromagnetism in semiconductors and exploring new p‐orbital physics and chemistry. In addition, the material shows elastic‐mechanoluminescence that may enable unprecedented mechano‐photonic‐spintronics.